Brevundimonas Bactremia - A Rare Case Report in Diabetic Patient - Arnaw Kishore, (International Journal of Medical Research, 2014)
Brevundimonas vesicularis is infrequently isolated from clinical sample in patient with or without immunosuppression. A 51 year old patient having diabetes with Coronary Artery Disease with Double Valve Disease and Peripheral Vascular Disease is described. The blood culture of the patient was positive after 24 hours by Biomerieux BacT/Alert 3D 60. Identified was done by API ID 32 G automated system. There is a little literature that supports isolation of B. vesicularis from a clinical specimen in India. After overview of literature, it is suggested that third generation cephalosporin, piperacillin/ tazobactum and ciprofloxacin is effective in treating infection caused by B. vesicularis, while efficacy of ampicillin sulbactum has to be studied further.